CLINICAL SIGNIFICANCE OF CHANGES IN PRO- AND ANTI-INFLAMMATORY CYTOKINES IN PHYSIOLOGICAL PREGNANCY - Хамдамов Бахтиёр Зарипович; Турдиева Дилнавоз Олимовна; Сафаров Суннатулла Саторович (Bright Mind Publishing, 2025)
Pregnancy is a unique physiological condition accompanied by a profound restructuring of the woman's immune system aimed at ensuring immunological tolerance to the semi-allogenic fetus.